Recombinant Aspergillus fumigatus antigens Asp f 3 and Asp f 9 in liposomal vaccine protect mice against invasive pulmonary aspergillosis. Issue 31 (29th July 2022) - Slarve, Matthew; Holznecht, Nickolas; Reza, Hernan; Gilkes, Adrienne; Slarve, Ielyzaveta; Olson, Jon; Ernst, William; Ho, Sam On; Adler-Moore, Jill; Fujii, Gary
Highlights: Liposomal Vaccine protects mice against invasive aspergillosis. Protection is effective despite immunosuppression common to aspergillosis patients. Protection is robust to multiple azole-resistant fungal strains. This vaccine may have promise for clinical applications. Abstract: Invasive pulmonary aspergillosis caused by the ubiquitous mold Aspergillus fumigatus is a major threat to immunocompromised patients, causing unacceptably high mortality despite standard of care treatment, and costing an estimated 1.2 billion annually. Treatment for this disease has been complicated by the emergence of azole resistant strains of A. fumigatus, rendering first-line antifungal therapy ineffective . The difficulties in treating infected patients using currently available drugs make immunotherapeutic vaccination an attractive option. Here, we demonstrate the efficacy of VesiVax® adjuvant liposomes, consisting of a combination of two individual liposome preparations, to which two recombinant A. fumigatus surface antigens, Asp f 3 and Asp f 9 (VesiVax® Af3/9), have been chemically conjugated. Using a murine model, we demonstrate that VesiVax® Af3/9 is protective against infection by azole resistant strains of A. fumigatus in both steroid-suppressed and neutropenic mice as quantified by improved survival and reduced fungal burden in the lungs. This protection correlates with upregulation of IL-4 produced by splenocytes, and the presence of Asp f 3 and Asp f 9 specific IgG2a antibodies in the serum of mice given VesiVax® Af3/9. Furthermore, mice given VesiVax® Af3/9 with a subsequent course of liposomal amphotericin B (AmBisome®) had improved survival over those given either treatment alone, indicating a benefit to VesiVax® Af3/9 vaccination even in the case of infections that require follow-up antifungal treatment. These data demonstrate that prophylactic vaccination with VesiVax® Af3/9 is a promising method of protection against invasive pulmonary aspergillosis even as the changing face of the disease renders current therapies ineffective.